ANALYSIS OF INCOME AND FEASIBILITY OF RICE-FISH ORGANIC FARMING (CASE STUDY IN JABUNG VILLAGE, TALUN DISTRICT) - Zamrodah, Yuhanin; Prayudhi, Luhur Aditya (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2025)
In order to increase agricultural production, especially food crops, it can be done by diversification. Where one form of diversification is by trying to combine food farming with other farming businesses, fish or more precisely called an integrated farming system. An integrated farming system is a method of fish cultivation combined with rice farming in the same land which must lead to increased efficiency of land use, because various types of businesses are applied. This integrated farming system or rice-fish farming is a novelty that is being tried at the research site. The purpose of this study is to analyze the level of production costs, income and profits in this organic rice-fish farming business. This research was conducted in Jabung Village, Talun District, Blitar Regency and used farming business analysis (costs, income and efficiency). The results of the study showed that   the total production cost of pattern I was Rp 11,346,982 per ha and pattern II was Rp 9,313,160 per ha. The average total income of pattern I was Rp 32,440,000 per ha and pattern II was Rp 27,700,000 per ha. The average income of pattern I was Rp 20,233,018 per ha and pattern II was Rp 17,526,840 per ha. The R/C Ratio results obtained values in pattern I (2.96)> 1 and pattern II (2.97)> 1. Thus, this organic fish and rice farming business is efficient and profitable, so it is worth continuing the farming business.